MobiCon: A Mobile Context-Monitoring Platform. (Communications of the ACM, 2012)
The article focuses on research into a practical context-monitoring system for use in context-aware applications for mobile devices. It states the MobiCon middleware framework would mediate personal sensor networks and context-aware applications while providing a runtime environment for applications and providing application programming interfaces (API). It comments that context-monitoring platforms need to provide application developers with intuitive, generic context-monitoring API which facilitate applications to delegate complex context-monitoring tasks to the system while dealing with application-specific logistics. It talks about how energy consumption is reduced by hierarchical sensor management that avoids continuous operation of high-power systems that drain energy.